PEMASARAN TERPADU TELUR AYAM RAS DI PT HARIM FARMSCO - Sri Yenny Pateda; Fauzan Zakari (Fakultas Peternakan Universitas Wijaya Kusuma Purwokerto, 2022)
The research objective was to determine the integrated marketing (marketing mix) of broiler eggs at PT. Harim Farmsco Pulubala. The research was located at PT Harim Faramsco in Pulubala District, Gorontalo Regency. The location was determined using a purposive sampling technique, which is based on the consideration that PT Harim Farmsco is the largest company and the largest supplier of purebred chicken eggs in the Gorontalo Regency area. The research method used is the case study method, data collection techniques through observation, interviews guided by a questionnaire. Data sources include primary and secondary data. Determination of the sample using total sampling at PT Harim Farmsco. The data analysis used is descriptive analysis, namely describing or describing the results of data processing into information that can be accounted for. The results showed that the average egg production produced was 1200 tubs or 36 000 eggs/ day, the prevailing price ranges from IDR 30 000 – IDR 65 000 / tub which is based on the size and quality of the eggs. The marketing reach covers provincial areas and areas outside the province such as the Kotamubagu area - North Sulawesi, the distribution channels used are direct and indirect distribution channels. Egg marketing with direct distribution channels is only limited to the area closest to the company's location with the quality of the eggs being marketed are cracked eggs which cost IDR 300 000 / tub. Promotions implemented at PT Harim Faramsco Pulubala are business to business and personal selling strategies.